Coping Strategies of Selected Filipino Nurses from the Risk of Stress Amidst the COVID-19 Pandemic 2019-2020: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
COVID-19 has affected the life and health of every individual across the world. Nurses are under stress, fear, tiredness, isolation, and persistent emotional trauma due to the COVID-19 pandemic. Continuous stress and trauma negatively influence their mental health, safety, and capacity to offer the best care possible. Nurses are on the front lines and are accountable for providing comprehensive care to various patient populations. Nurses play a significant role in healthcare systems since they constitute the bulk of healthcare practitioners. The study aimed to determine the coping strategies selected Filipino nurses adopted to manage their stress and stressful situations during the COVID-19 pandemic.   The study used a quantitative approach and a descriptive research design and was administered to fifty (50) randomly selected Filipino nurses around Metro Manila. Furthermore, this study utilized a snowball and convenience sampling technique to determine the study's respondents. The data was gathered through a survey questionnaire aligned with the problem statement. The researchers developed a self-formulated questionnaire, and the revision was done after considering the suggestions and recommendations of the validator and the research adviser. To validate the instrument, the researcher pre-tested the survey questionnaire on six (6) Filipino nurses who were not included in the study to test the reliability and validity. Researchers prepared all the necessary permits before conducting the survey and gathered the data through Google Forms. Researchers used frequency of data, ranking, and weighted mean for the statistical data treatment. Fifty (50) selected Filipino nurses responded to a self-administer questionnaire comprising three parts, each with a fifth of teen items (15). The results demonstrated in the first part are Emotionally-Focused Strategies, while the second and third categories are labelled as Problem-Focused Strategies of coping. The data gathered indicate that all three ranked one item has a High Coping Strategy level.